Exploring The Factors Influencing Learners’ Attitudes and Engagement Towards Learning Outcomes in Araling PanlipunanAmong Grade 10 Learners - Gonzales, Bernadette T.; Hermosa, Jherwin P. (Future Science / FSH-PH Publications, 2023)
his study aimed to discern the factors influencing attitudes and engagement towards learning Araling Panlipunan in terms of instructional methods, classroom environment, the difficulty of the subject, teachers' behavior, learning resources, teaching competency, learning style, and integration of technology. Moreover, it also determined the level of the learning outcomes in Araling Panlipunan as cognitive, behavioral, and attitudinal. The study utilized a descriptive research design to collect quantifiable information that can be used to make statistical inferences about the target audience through data analysis. Stratified Random Sampling was used to identify 127 grade 10 learners from San Isidro Integrated National Highschool in the Schools Division of Lipa City. The data were gathered using a survey questionnaire which was validated with the help of the experts. Findings revealed that there is a significant relationship between instructional methods and the learning outcomes in Araling Panlipunan as to Cognitive, Behavioral, and Attitudinal. The classroom environment was found to have highly significant relationships with cognitive, behavioral, and attitudinal learning outcomes in Araling Panlipunan. The difficulty of the subject has a highly significant relationship with cognitive and attitudinal learning outcomes. As for teacher behavior, highly significant relationships were recognized about cognitive, behavioral, and attitudinal Learning Outcomes in Araling Panlipunan. However, after all the data was gathered and calculated, the result revealed that there is no significant relationship between the Difficulty of the Subject and Behavioral Learning Outcomes in Araling Panlipunan.